Incidence of Anesthesia-Associated Cardiac Arrest And Related Factors At Srinagarind Hospital - Boonmak, Polpun; Boonmak, Suhattaya; Srechaipanha, Somyong; Thincheelong, Viriya (Srinagarind Medical Journal, 2013)
Abstract Objective: To identify the incidence of anesthesia-related cardiac arrest complications and related factors. Design: Prospective, descriptive study. Methods: This was part of a multi-center study conducted by the Thai Royal College of Anesthesiologists for surveillance of anesthetic-related complications in Thailand in 2003. We collected data from all of the cases receiving anesthesia service at Srinagarind Hospital between January 1 and December 31, 2003, to report the incidence of cardiac arrest and analyze the causes in order to improve the quality of service. Events of cardiac arrest were reported by the attending anesthesia personnel and anesthesiologists. All the forms were checked and verified by the principal author then included in the study. Results: 10,601 patients were included in this study. The incidence of cardiac arrest was 47 (44.33 per 10,000 95%CI 32.59, 58.91). The most common cause was hypotension (53.19%) while contributing factors included emergency situation (29.67%), poor patient preparation (16.48%), lack of experience (15.38%) and inappropriate decision-making (12.09%). The suggested corrective strategies were quality assurance activity and additional training. Conclusion: The most common cause of cardiac arrest during anesthesia at Srinagarind Hospital was hypotension from massive blood loss. Preventive and corrective strategies would include quality assurance activities that involve personnel development and the provision of sufficient equipment. Keywords: Complication; Cardiac Arrest; Anesthesia; Incidence